CHAOS AND MUSIC - ANDREICA, Oana (Studia Universitatis Babes-Bolyai Musica, 2008)
The Chaos theory describes an unpredictable behavior that occurs in a system that should be governed by deterministic laws. Such systems are highly sensitive to initial conditions, and a very small initial difference makes an enormous change to the future state of the system. Originally, the theory was used to describe the unpredictability in meteorology, but it has been extended to other branches of science. Borrowed from Mathematics, the term “stochastic”, which means the calculus of probabilities, has also been applied to the music that contains elements of chaos. Iannis Xenakis used it for musical procedures whereby overall sound contours are determined, but inner details are left to chance or worked out mathematically by the composer or by the computer. Another composer who used the laws of chaos in his music was György Ligeti best known for his thick orchestral clusters.